Collaboration of the Eco Art Garden as an Effort to Foster Students’ Creativity through a Participatory Method at a Senior High School in Banten, Indonesia - Pina Merlina; Indriati Dhiya Ulhaq; Siti Laysa Nurfauziyah; Fitri Novianti; Nabila Lailil Widiastuti; Ika Rifqiawati (Jurnal Pendidikan Abad Ke-21, 2025)
This study aimed to describe the implementation of the Eco Art Garden project as an effort to foster students’ creativity through a participatory method a Senior High School in Banten, Indonesia. The two-week activity involved 56 students and eight facilitators in a manner applicable in the participatory method in which students took an active part in planning, implementation, and evaluation. In week one, the students made mosaic artworks using recycled materials, while in week two, they made a vertical garden using plastic bottles in forms involving cleaning, cutting, and painting. The impact of the study indicates that the participants were actively involved in all implementation levels and managed to produce seven pieces of mosaic artwork and one vertical garden erected in the school compound. Conclusion Conclusion Based on these impacts, it is clear that Eco Art Garden is an important environmental subject for meaningful environmental-based educational activities related to increasing student creativity by involving them in processing waste materials and creating art.